Formal multiplicative root series and algorithms of their evaluation. Issue 8 (7th July 2021) - Gan, Xiao-Xiong; Bugajewski, Dariusz
Abstract: In this paper we provide necessary and sufficient conditions for a formal power series g over R or C to have formal power series g 1 / k such that ( g 1 / k ) k = g for all positive integers k or for some positive integers. The algorithms of computing such formal root series are also provided. Moreover, we investigate the uniqueness of formal root series if there exists.